Two polymorphs of remdesivir: crystal structure, solubility, and pharmacokinetic study. Issue 16 (9th April 2021) - Yu, Kaxi; Chen, Shuai; Amgoth, Chander; Tang, Guping; Bai, Hongzhen; Hu, Xiurong
Abstract : Here it deliberates the relationships between explicit crystal structures and biopharmaceutical properties of two polymorphs of remdesivir. Abstract : Two polymorphic phases of the antiviral drug remdesivir (RDV), namely RDV-I and RDV-II are prepared and structurally characterized by single-crystal X-ray diffraction. Both RDV-I and RDV-II are solvent-free but exhibit different packing patterns in their crystals. RDV-I and RDV-II feature different pharmacokinetics, as revealed by in vitro and in vivo studies. This work highlights the significance of remdesivir drug formulations on the pharmacokinetics and ultimately patient outcome when combating the coronavirus disease 2019 (Covid-19).